CHARACTERISTICS ANALYSIS OF THE STUDY MATERIALS REQUIRED FOR MEN COAT PRODUCT - OANA Ioan Pavel; OANA Dorina; KENYERES Florentina (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2014)
Garments is a means of artistic creation with not only the function of defense of the body and regulating physiological functions, but also by its beautifying. In order to achieve men coat product, we have the possibility to choose the material from a group of three materials that are completely different of yarn contents. After comparing measurements made for three types o f materials were found in the composition of the material has a higher percentage of wool meets most conditions necessary for wearer comfort so is the material most commonly used to make the clothing for winter season. After comparing measurements made for three types of materials were found in the composition of the material has a higher percentage of wool meets most conditions necessary for wearer comfort so is the material most commonly used to make the clothing for winter season. The difference between the material properties and material transformation phases in the product have been presented in order to emphasize the need for close co-working between professionals involved in making a fashion product from yarn, yarn, fabric and garment finishing product. The types of materials used for making winter outer wear products greatly influences the design and technological design processes in their turn textiles are directly dependent on the characteristics by their structure. The difference between the material properties and material transformation phases in the product have been presented in order to emphasize the need for close co-working between professionals involved in making a fashion product from yarn, yarn, fabric and garment finishing product.